Temperature dependences of SnTe linear expansion coefficient - Rogacheva, E.I.; Popov, V.P.; Nashchekina, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The influence of kinetic factors on the temperature dependences of the linear expansion coefficient (a) for SnTe crystals with different degrees of deviation from stoichiometry was studied. The a(T) dependences were obtained by using stationary and dynamic regimes. In the case of the stationary regime, an increase in with increasing temperature (4.2-300 K) was registered, and anomalies in the a(T) dependences were observed and attributed to phase transitions. After quick plunging into liquid nitrogen and subsequent heating the samples up to 300 K without keeping them for a long time at fixed temperatures (a dynamic regime), the a(T) dependences exhibited an oscillatory behavior, most pronounced in the sample with 50.4 at.% Te. It is suggested that the observed behavior of the a(T) dependences is connected with an oscillatory process of approaching the equilibrium in the intrinsic defect subsystem and with overlapping of relaxation processes and temperature phase transitions.